Antimicrobial mechanism and the effect of atmospheric pressure N2 plasma jet on the regeneration capacity of Staphylococcus aureus biofilm. Issue 8 (14th September 2018) - Wang, Jiaquan; Yu, Zhiyuan; Xu, Zimu; Hu, Shuheng; Li, Yunxia; Xue, Xiaojuan; Cai, Qiuchen; Zhou, Xiaoxia; Shen, Jie; Lan, Yan; Cheng, Cheng
Abstract: This study systematically assessed the inactivation mechanism on Staphylococcus aureus biofilms by a N2 atmospheric-pressure plasma jet and the effect on the biofilm regeneration capacity from the bacteria which survived, and their progenies. The total bacterial populations were 7.18 ± 0.34 log10 CFU ml −1 in biofilms and these were effectively inactivated (>5.5-log10 CFU ml −1 ) within 30 min of exposure. Meanwhile, >80% of the S. aureus biofilm cells lost their metabolic capacity. In comparison, ∼20% of the plasma-treated bacteria entered a viable but non-culturable state. Moreover, the percentage of membrane-intact bacteria declined to ∼30%. Scanning electron microscope images demonstrated cell shrinkage and deformation post-treatment. The total amount of intracellular reactive oxygen species was observed to have significantly increased in membrane-intact bacterial cells with increasing plasma dose. Notably, the N2 plasma treatment could effectively inhibit the biofilm regeneration ability of the bacteria which survived, leading to a long-term phenotypic response and dose-dependent inactivation effect on S. aureus biofilms, in addition to the direct rapid bactericidal effect.